Transformation of Educational Institution Management at Ilyas Karanganyar Islamic Boarding School - Purbiyanto, Eko; Pamungkas, Tri (Politeknik Harapan Bangsa Surakarta, 2024)
Organizational transformation program is a strategic step that is not only an option, but also a necessity to ensure the sustainability and competitiveness of a company or organization. This transformation is closely related to the overall strategy, and often includes total changes involving all aspects of the organization, resulting in a completely new entity that is more adaptive to environmental changes. This transformation is very important so that the vision and mission of the organization can be realized optimally. This study aims to analyze the transformation process carried out by the Ilyas Karanganyar Islamic Boarding School, which includes the steps of planning, organizing, mobilizing, and supervising. The data sources in this study came from direct observation, interviews with related parties, and internal document analysis. The research method used is a qualitative approach with case studies to identify key findings related to productive, efficient, and effective collaboration in achieving common goals. The research findings show that innovation and change in education are key factors in increasing organizational competitiveness amidst the dynamics of ever-growing change.